Biodentine™ Partial Pulpotomy of a Young Permanent Molar with Signs and Symptoms Indicative of Irreversible Pulpitis and Periapical Lesion: A Case Report of a Five-Year Follow-Up - W. Chinadet; T. Sutharaphan; P. Chompu-inwai (Hindawi Limited, 2019)
The purpose of this paper was to report the five-year success of Biodentine™ partial pulpotomy in a young permanent molar, with signs and symptoms indicative of irreversible pulpitis and periapical lesion, in a nine-year-old girl. Preoperative clinical examination revealed a large carious lesion of the left mandibular permanent first molar. The patient reported pain on percussion. The tooth responded positively to the electric pulp test and had lingering pain after cold testing. A periapical radiograph showed a deep carious lesion and periapical lesion. Based on the clinical and radiographical examination, the tooth had signs and symptoms indicative of irreversible pulpitis and periapical lesion. During caries removal, pulp exposure occurred, and 2-3 mm in depth of pulp tissue at the exposure site was removed. Haemorrhage was controlled within four minutes with 2.5% sodium hypochlorite-moistened cotton pellets. Biodentine™ was then applied as both a pulp dressing and a temporary restoration. At the following visit, composite resin was placed over the Biodentine™ as a final restoration. During a five-year follow-up, the tooth was asymptomatic, had positive responses to sensibility tests, and had no discolouration. Follow-up radiographs showed a dentine bridge and periapical healing.